Corporate Social Responsibility and Organizational Performance of Cooperative Unions in Mbale City: A Case of Bugisu Cooperative Union - Ididi Richard (Uganda Christian University, 2024)
The research was undertaken to assess the Impact of corporate social responsibility on organizational performance of cooperative unions in Mbale city. It was guided by three objectives; to determine the effect of leadership style on organizational performance of Bugisu Cooperative Union to analyze the effect employee engagement on organizational performance of Bugisu Cooperative Union, to assess the effect of ethical practices on organizational performance of Bugisu Cooperative Union. The researcher used a sample size of 45 respondents and used questionnaires to collect data and later the data was analyzed using the statistical package for social sciences (SPSS). Results of the first objective showed that leadership style has a significant effect on organizational performance of Bugisu Cooperative Union. Supported by the following responses; 80% were positive to the statement that leadership style fosters employee motivation; 66.6% who were also the majority were positive to the statement that it promotes a proactive organizational culture; 62.3% who also constituted the majority were positive to the statement that servant leaders create a supportive work environment that encourages collaboration. Results of the second objective revealed that employee engagement has a significant effect on organizational performance of Bugisu Cooperative Union. Supported by the following responses; 66.7% of the respondents were positive to the statement that engaged employees tend to be more motivated, innovative, and committed, leading to greater organizational success and profitability, 66.6% forming the majority were positive to the statement that higher engagement levels enhance organizational performance by fostering employee well-being and motivation. Results of the third objective showed that that ethical practice have a significant effect on organizational performance of Bugisu Cooperative Union. 73.4%forming the majoritywere positive to the statement that ethical practices can positively impact not only employee and consumer perceptions but also financial outcomes, 51.1% were positive to the statement that ethical leadership fosters a climate of trust and openness, resulting in higher employee commitment. Leaders should uphold high ethical standards and serve as role models for ethical behavior. Demonstrating integrity, fairness, and transparency in decision-making and actions sets the tone for the entire organization and fosters a culture of ethics.